Pengaruh Budaya Organisasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada Karyawan Di Cv. Spp Corporation Tasikmalaya) - Purnama, Gilang Sandi (BISMA : Business and Management Journal, 2023)
This study aims to determine the effect of organizational culture and job satisfaction simultaneously on employee performance at CV. SPP Corporation. The effect of organizational culture and job satisfaction partially on employee performance at CV. SPP Corporation. The method used in this research is associative with a quantitative approach. With a research sample of 35 people as respondents to CV. SPP Corporation based on 35 known population data. The data used is primary data. The analytical tool used in this study is multiple linear regression using the SPSS support application version 25. The test results show that simultaneously organizational culture and job satisfaction have a significant effect on employee performance. Partially organizational culture variables have a significant effect on employee performance, as well as job satisfaction variables partially have a significant effect on employee performance